Introducing project-based learning steps to the preschool teachers in Bandung, Indonesia - Devi Pratami; Nor Hasrul Akhmal; Muhd Ikmal Isyraf Mohd Maulana; Syed Ahmad Helmi Syed Hassan (Journal of Technology and Science Education)
The Merdeka Belajar curriculum is the current curriculum developed by Indonesian Ministry of Education which should be implemented thoroughly in 2024. Project-based learning is identically engaged with this curriculum which offers many advantages to enrich the quality of education. This has been promoted and already implemented in several schools across the region in Indonesia, yet many teachers are still finding it was difficult to be applied. This research explores the project-based learning steps for preschool teachers in Bandung using community service program by Industrial Engineering lecturers in Indonesia. There were 42 participants from different kindergarten schools who joined in the PJBL workshop. With an active learning workshop delivery, a significant result has been achieved that it could increase their understanding of PJBL concept. “A Healthy House” project was taken as the example of the topic in the workshop. To check the participant’s understanding of the PjbL steps, the questionnaire was distributed two times, before and after the workshop ended. Using t test, the workshop of PJBL has significantly impacted the teachers. They were able to understand the principles of PjBL and the steps of the methods.